Implementasi Pembelajaran Inklusif Multikultural dalam Pembentukan Karakter Budi Pekerti Siswa Studi Kasus di Min 2 Gunungkidul Yogyakarta: Studi Kasus di MIN 2 Gunungkidul Yogyakarta - Defi Firmansah; Pitaloka Jati Kumolo Dewi; Heru Saiful Anwar (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2026)
Multicultural education offers hope in addressing various social tensions that have emerged in recent times, as it is an educational approach that consistently upholds values, beliefs, heterogeneity, plurality, and diversity in all aspects of education. This study aims to describe the implementation of multicultural inclusive learning in developing students’ moral character and to identify the challenges of its implementation at MIN 2 Gunungkidul Yogyakarta. The study employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation involving the principal, teachers, and students as sources of information. The data were analyzed through data collection, data reduction, data display, and conclusion drawing or verification. The findings show that multicultural inclusive learning was implemented through the habituation of the 5S values (smiling, greeting, addressing, politeness, and courtesy), inclusive classroom arrangement for students with special needs, and the strengthening of discipline, responsibility, independence, care, and religious activities within the madrasah environment. These practices contributed to a warmer learning atmosphere, acceptance of differences, and social interaction between regular students and students with special needs. The main challenges included the limited availability of special assistant teachers, teachers’ limited competence in handling students with special needs, and insufficient inclusive learning facilities